2021
DOI: 10.15446/dyna.v88n218.92055
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline delignification of lignocellulosic biomass for the production of fermentable sugar syrups

Abstract: The objective of this study to analyze the effect of alkaline pretreatment on the structure, composition, and subsequent hydrolysis of agricultural wastes.  An increase in the content of reducing sugars after the pretreatment is achieved. Its effectiveness is confirmed, offering a practical procedure to produce alternative energy. Factors such as the calcium hydroxide concentration (0.1 and 0.5g Ca(OH)2/g-dry matter), liquid to solid ratio (12 and 28ml/g-dry matter), temperature (40 and 70°C), stirring rate (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Alkali application is able to alter the structure of lignin by degrading ester and glycosidic side chains, cellulose swelling, and partial cellulose recrystallization (Kim et al 2014). Previous studies on alkaline pretreatment have shown its effectiveness in a variety of modes and conditions with treatment times on the order of hours and days rather than minutes or seconds (Fuertez-Córdoba et al 2021). In this work, sodium hydroxide pretreatment showed the highest performance in delignification process, followed by calcium hypochlorite, and sulfuric acid pretreatments.…”
Section: Pretreatment Performance On Delignificationmentioning
confidence: 68%
See 1 more Smart Citation
“…Alkali application is able to alter the structure of lignin by degrading ester and glycosidic side chains, cellulose swelling, and partial cellulose recrystallization (Kim et al 2014). Previous studies on alkaline pretreatment have shown its effectiveness in a variety of modes and conditions with treatment times on the order of hours and days rather than minutes or seconds (Fuertez-Córdoba et al 2021). In this work, sodium hydroxide pretreatment showed the highest performance in delignification process, followed by calcium hypochlorite, and sulfuric acid pretreatments.…”
Section: Pretreatment Performance On Delignificationmentioning
confidence: 68%
“…Size reduction may provide better results but very fine particle size may impose negative effects on the subsequent processing such as enzymatic hydrolysis. Effectiveness of pretreatment was determined the substrate structure and composition of lignocellulosic biomass as well as pretreatment conditions (Fuertez-Córdoba et al 2021). Pyrolysis is an endothermic process where less input of energy is required.…”
Section: Pretreatment Performance On Delignificationmentioning
confidence: 99%
“…Alkaline pretreatment involves the utilization of alkaline bases such as sodium hydroxide (NaOH), potassium (KOH), calcium hydroxide (Ca( OH) 2 ) , and ammonia hydroxide (NH 4 OH), among others. A notable feature is its operation under mild temperature and pressure conditions, minimizing sugar degradation and inhibitory compounds formation [12,95]. The primary outcome of alkaline pretreatment is disintegration of the cell wall, which is achieved by dissolving polysaccharides and inducing chemical swelling, leading to the disruption of linkages between lignin and carbohydrates, ultimately removing lignin.…”
Section: Alkaline Pretreatmentmentioning
confidence: 99%
“…Pretreatment of lignocellulosic biomass involves partial delignification, and then depolymerization of hemicellulose, using appropriate reagents and optimal pretreatment conditions [33]. Delignification and depolymerization of hemicellulose increases biomass porosity, which during sorbent synthesis will enable better accessibility of agents for more efficient conversion of cellulose to the desired product.…”
Section: Pretreatment Of Lignocellulosic Biomassmentioning
confidence: 99%